2019
DOI: 10.3390/cancers11081041
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Vaccines: Research and Applications

Abstract: Designing cancer vaccines has been at the forefront of cancer research for over two-and-a-half decades. In particular, delivery methods used to stimulate effective and long-lasting immune responses have been the major focus. This special issue presents new tumor associated antigens, delivery methods, combination immune therapies, methods of measuring immunity induced following cancer vaccinations, and mechanisms in understanding tumor microenvironments and immunosuppression—all beneficial for the design of imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 36 publications
(36 reference statements)
0
19
0
Order By: Relevance
“…The vaccination method can be immune cell-mediated, using antigen presenting cells such as dendritic cells, peptide based or nucleic acid based ( 162 , 163 ). As a whole, these methods have shown exciting pre-clinical data and interesting early phase trials with limited activity in monotherapy.…”
Section: Improving Immunotherapy Efficacy: Beyond Immune Checkpoint Inhibitorsmentioning
confidence: 99%
“…The vaccination method can be immune cell-mediated, using antigen presenting cells such as dendritic cells, peptide based or nucleic acid based ( 162 , 163 ). As a whole, these methods have shown exciting pre-clinical data and interesting early phase trials with limited activity in monotherapy.…”
Section: Improving Immunotherapy Efficacy: Beyond Immune Checkpoint Inhibitorsmentioning
confidence: 99%
“…This kind of therapeutic approach is what we know as a cancer vaccine. 70 Arbelaez et al developed long synthetic peptides (SLPs) against neoepitopes of G12C, G12V, and G12D KRAS-mutant variants. They also conjugated cationic lipoplexes to every SLP to facilitate the delivery of these peptides to secondary lymph organs, eliciting activation of CD4+ T-cells but of CD8+ T-cells as well.…”
Section: Krasmentioning
confidence: 99%
“…Using genetic engineering techniques like CRIPS/Cas and TALEN, 74 the endogenous TCR can be silenced, and then, transduction of a new laboratory-designed TCR construct can be done for another expression on T-cells and induction of a specific response against cells presenting certain HLA-epitope complexes derived from KRAS-mutant variants. 75 …”
Section: Krasmentioning
confidence: 99%
“…Indeed, Exosomes are cell-free mediators of the immune system which act for intercellular connection. The administration of allogeneic exosome cancer vaccines would lead to a roadmap toward personalized immunology therapies [29,30]. Some other studies demonstrated the therapeutic potentials of autologous heat shock protein (HSP) for cancer vaccines.…”
Section: Cancer Vaccinementioning
confidence: 99%